Socio-economics of wheat production in Kailali and Sunsari districts of Nepal - Subedi, Sanjiv; Ghimire, Yuga N.; Devkota, Deepa; Kharel, Meena; Gautam, Sudeep; Sharma, Bimala; Sapkota, Bidya Kiran (Journal of Agriculture and Natural Resources, 2020)
For socio-economic assessment on wheat production, research was conducted from March to June, 2019 in two major wheat growing districts of Nepal, Kailai and sunsari. The primary information was collected by face to face interview using the pre-tested semi-structured interview schedule, two Key Informant Surveys were also done.In addition, the secondary information were collected from the review of related literatures. The survey areas were selected by consultating with Agriculture Knowledge Centre and agricultural officials of the local government; sample were selected by using simple random sampling. All total, 194 samples were selected for this study; the outliers and incomplete responses were omitted. The descriptive statistics revealed that Nepal 297 (66.16 %) has the highest area coverage in Sunsari while Gautam (36.50%) has the highest coverage in Kailali. Multiple regression model revealed that wheat cultivated area (p= 0.000), adoption of NARC released varieties (p= 0.000), gender of the household head (p= 0.017), age of the household head (p= 0.040), membership of organization (p= 0.094) and number of family members between age group 15 to 59 years (p= 0.085) have significant effect on wheat production. Furthermore, the unpaired t-test showed that the mean productivity of wheat in Kailali (2.99 Mt./ha) is significantly higher than that of Sunsari (2.81t./ha) at 5% level of significance. To increase the wheat productivity, the concerned government agricultural institutions should: assure access to NARC released improved varieties, make policy to consolidate the fragmented land, encourage the economically active population and the household heads towards wheat production by providing the efficient technical and financial support.